Tekanan Darah Sebagai Indikator Klinis Kecepatan Pemulihan Kesadaran Setelah Anestesi Umum - Aric Frendi Andriyan; Ikshan Amran; Leo Agustigno; Dewi Frendi Siska; Donna Handayani (JKM : Jurnal Keperawatan Merdeka, 2026)
Background: Delayed emergence from anesthesia is an undesirable event in anesthetic practice. One of the contributing factors is the patient’s blood pressure. Abnormal blood pressure can interfere with the elimination of anesthetic agents, potentially prolonging the time to regain consciousness. This study aims to determine the relationship between postoperative blood pressure and emergence time in patients undergoing general anesthesia at RSI Siti Rahmah Padang. Methods: This study was an analytical observational research with a cross-sectional design. Data were collected at RSI Siti Rahmah Padang from November 1, 2023 to January 11, 2024 using the Aldrete Score observation sheet. A total of 66 respondents were selected using purposive sampling, Results: The results showed that 27.3% of patients were aged 36–45 years, 59.1% were female, and 56.1% had ASA I status. Additionally, 47% of patients had normal blood pressure, and 59.1% did not experience prolonged emergence time. A significant relationship was found between postoperative blood pressure and emergence time in patients undergoing general anesthesia (p = 0.000). Conclusion: There is a significant relationship between postoperative blood pressure and emergence time among patients receiving general anesthesia at RSI Siti Rahmah Padang.